Prediction on contaminant migration in aquifer of fractured granite substrata of landfill - Wang, Yang; Zhang, Ke-neng; Chen, Yong-gui; Zhou, Xing-zhi; Jin, Fu-xi (Journal of Central South University, 2013)
Nowadays, a certain amount of landfills in China were constructed without horizontal liner system. The research conducted focuses mainly on the contaminants from landfill leachate migrating in the aquifer of a fractured granite area, and pollution predictions for groundwater were made by establishing numerical model with Visual Modflow combining field investigation like geological surveys, drilling, geophysical explorations, hydrogeological experiments, water quality analysis. The transportation of the chloride ion from landfill in the aquifer was simulated in the model with time frames of 2 555, 3 650, 5 475 and 7 300 d. The model shows that from 2 555 d to 7 300 d starting from 2003, the chloride ion migrated from 900 m to 1 300 m, respectively, along the groundwater flow. The results indicate that as leachate plume migrated in the aquifer, the concentration of the pollutants can be up to 19.74 to 251.76 times that of background value. The research proves that the leachate poses a threat to the local water body and offers a reference towards groundwater pollution prevention for fractured granite landfill sites.